Kebiasaan Konsumsi Fast Food terhadap Obesitas pada Anak Sekolah Dasar Banda Aceh - Junaidi Junaidi; Noviyanda Noviyanda (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
Obesity in children due to excessive eating and high energy. The frequency of fast-food consumption in children and adolescents on average 1-2 times a week, with the kind of fast food is often consumed was fried chicken, french fries, and soft drink. The study aims to determine the relationship between habitual consumption of fast food and obesity in children. This research is descriptive analytic design with a case-control study, with a total sample of 64 children in primary schools 67 Banda Aceh. The research was conducted in primary schools 67 in Banda Aceh. Collecting data using questionnaires and measurements of height and weight, and the nutritional status of primary school students was taken by anthropometric indices BFA, then these data were analyzed using chi-square test. The results of the study the majority of fast food consumption amounted to 62,5% in obese children is frequent, and normal children rarely consume 68,7%. The statistical results obtained p-value (0,024). It can be concluded that there is an influence of fast food consumption habits on the incidence of obesity in primary school students. Suggestions for the school is expected to work closely with health professionals to provide nutrition counseling, particularly on the consumption of fast food to the students.